Estimasi kedalaman batuan dasar menggunakan metode inversi robust 2-D data geolistrik tahanan jenis konfigurasi dipole dipole di Bukit Apit Puhun Kecamatan Guguk Panjang Kota Bukittinggi (The estimation of the depth of the bedrock uses a robust 2-D inversion method of resistivity geoelectric data with a dipole dipole configuration at Bukit Apit Puhun, Guguk Panjang District, Bukittinggi City) - - Bavitra; - Akmam; Harman Amir (Department of Physics – Universitas Negeri Padang UNP, 2015)
Bukit Apit Puhun Bukittinggi area is located at Sianok fault zone. This area was potensially occur tectonic activity such as earthquakes. Tectonic activity could disturb the stability of the bedrock. The aim of this research was to determine the resistivity and to depth of basement bedrock in Bukit Apit Puhun Bukittinggi area. This research used Robust 2D inversion Geoelectrical data with Dipole-dipole configuration. The Data of this research were taken five track using ARES (Automatic Resistivitymeter). The data were processed and interpreted with using Robust 2D inversion. The result of this research showed that type of basement bedrock in Bukit Apit Puhun Guguk Panjang was an igneous groups, namely Andesite. Resistivity of Andesite bedrock were varies on the each track. The resistivy of Andesite was 352 Ωm – 7598 Ωm. Depht of Andesite bedrock were varies, which generally more than 30 meters deepness at Bukit Apit Puhun Bukittinggi area